Experimental studies on treated sub-base soil with fly ash and cement for sustainable design recommendations - Muthuramalingam, Jayakumar; Sing, L. (WORLD ACADEMY OF SCIENCE, ENGINEERING AND TECHNOLOGY (WASET), 2012)
The pavement constructions on soft and expansive soils are not durable and unable to sustain heavy traffic loading. As a result, pavement failures and settlement problems will occur very often even under light traffic loading due to cyclic and rolling effects. Geotechnical engineers have dwelled deeply into this matter, and adopt various methods to improve the engineering characteristics of soft fine-grained soils and expansive soils. The problematic soils are either replaced by good and better quality material or treated by using chemical stabilization with various binding materials. Increased the strength and durability are also the part of the sustainability drive to reduce the environment footprint of the built environment by the efficient use of resources and waste recycle materials. This paper presents a series of laboratory tests and evaluates the effect of cement and fly ash on the strength and drainage characteristics of soil in Miri. The tests were performed at different percentages of cement and fly ash by dry weight of soil. Additional tests were also performed on soils treated with the combinations of fly ash with cement and lime. The results of this study indicate an increase in unconfined compression strength and a decrease in hydraulic conductivity of the treated soil.